2020
DOI: 10.21608/ejfsat.2020.24770.1129
|View full text |Cite
|
Sign up to set email alerts
|

Possible Protective Potential of Atorvastatin and Black Seed (Nigella Sativa) Oil in Amikacin induced Nephrotoxicity in Adult Male Albino Rats

Abstract: Background and Objectives: Amikacin (AMK) has long been utilized as a gainful antibiotic in preventing Gram-negative infections. Despite all the profitable impacts, amikacin has significant nephrotoxic side effects. The possible protective effects of atorvastatin (ATO) and/or black seed (Nigella sativa) oil (NSO) were evaluated in rats with amikacin-induced acute renal damage, in which generation of reactive oxygen species plays a noteworthy role. Methods: Rats were treated with AMK (30 mg/kg body weight/day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…This histopathology findings revealed that AK 400 mg/kg was associated with disturbances in the kidney histopathological picture, including inflammatory cell infiltration, tubular epithelial lining degeneration, and tubular necrosis. These results agree with Abdel Fattah and Gaballah, (2020), who demonstrated that marked degenerative changes in the kidney and marked tubular necrosis occurred with AK [ 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…This histopathology findings revealed that AK 400 mg/kg was associated with disturbances in the kidney histopathological picture, including inflammatory cell infiltration, tubular epithelial lining degeneration, and tubular necrosis. These results agree with Abdel Fattah and Gaballah, (2020), who demonstrated that marked degenerative changes in the kidney and marked tubular necrosis occurred with AK [ 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…Rats of groups 2 and 4 received 400 mg/kg body weight NSO by oral gavage for 15 consecutive days started 24 h before radiation exposure [ 20 ].…”
Section: Methodsmentioning
confidence: 99%